Распределение металлической фазы в синтетических алмазах типа «карбонадо» - Ножкина, А.В.; Лаптев, А.И.; Ермолаев, А.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Studying of a structural structure synthetic «carbonado» is spent by a method of electronic scanning
microscopy. It is established, that the surface «carbonado» is covered by the large diamond crystals
reaching 200 microns, having obviously expressed structure of growth. On a surface of these crystals observed
drops of metal-catalyst (nickel) of a submicronic range. It is established, that the structure synthetic
«carbonado» represents interpenetrating skeletons from diamond and ceramic-metal phases.